Pengaruh Kualitas Layanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada 90’s Kid Barbershop Maumere - Oktavianus Rikardo Duu Fernando; Yoseph Darius P. Rangga; Nunsio H. Meylano (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This study aimed to (1 ) determine the description of Customer Loyalty, Service Quality, and Customer Satisfaction; (2) analyze the effect of Service Quality and Customer Satisfaction on Customer Loyalty both partially and simultaneously.The population in this study were customers who received services at 90's Kid Barbershop Maumere. The sample in this study used the Cochran formula totaling 96 people. Data were collected through questionnaires and analyzed using descripive metro and inferential statistics namely multiple linear regression. Hypothesis testing was cat out through the F test and t-test.The results of the descriptive analysis showed that the Customer Loyalty variable was in the good criteria, the Service Quality variable was in the fairly good criteria, and the Customer Satisfaction variable was in the good criteria. The statistical results of the t-test showed that the service quality variable partially did not have a significant effect on the customer loyalty variable. Furthernmore, partially the customer satisfaction variable does not significantly affect the customer loyalty variable. The results of the f-test statistics show that the service quality and customer satisfaction variables significantly affected customer loyalty. The results of the determination analysis show that the two independent variables in this study can explain that the level of relationship between the independent variables and customer loyalty is interpreted as low.